A Proposal of a Combined Convergence Regulatory Strategy Applied to Post-approval Changes by Latin American Countries, Reducing Workload and Allowing Continuous Improvement to Guarantee the Quality, Safety, and Efficacy of Medicines - Rodriguez, Heraclio; De Lucia, Maria Lucia (Frontiers in Medicine, 2021)
.Post approval changes (PACs) for medicinal products have been showing an add up through the years faster than the capacity of the NRAs to adapt their resources to attend the lifecycle demand without any negative impact. Due to the regulatory management of PACs has become a critical point when evaluating the efficiency and effectiveness of the NRAs, we present this proposal based on the analysis of the data available of the total PACs evaluated and the timeline invested for some NRAs of Latin America. Methodology: A retrospective search in official websites of the competent NRA of 14 Latin America countries (Mexico, Guatemala, Nicaragua, Honduras, El Salvador, Panamá, Costa Rica, Venezuela, Colombia, Ecuador, Peru, Argentina, Chile and Brazil) was done to collect data registered related to PACs during last 4 or 6 years, until January 2021. The NRAs with data registered available and considered for this analysis were (ANVISA - Brazil, COFEPRIS-Mexico, INVIMA- Colombia - and Ministry of Health - Costa Rica The data collected analysis was focused on PACs required to be approval before implementation, PACs submitted or PACs submitted and approved,(according the data reported per NRA), for Small molecules, biologic, and Biotechnological products.. Results and Discussion: Based on the data registered in the websites searched, we found a total of 47.182 post approval changes evaluated by ANVISA-Brazil, during 2016 until January 2021; 1272 by COFEPRIS-Mexico during 2014 until 2016; 22.780 by INVIMA-Colombia during 2000-2020 and 16.269 by Costa Rica´s Ministry of Health. The results gotten, let infer that there were differences in the regulatory processes and procedures applied by the ANVISA, INVIMA, COFEPRIS and MOH of Costa Rica., impacting directly on the implementation of PACs, creating delay of its scheduled supply putting in risk continuity of chronic therapies, with serious consequences for the patients. Recommendations: Latin America NRAs in their endeavors in the optimization of their resources and also to ensure continuity of medicine supply for the patients, could implement regulatory pathways such as reliance or recognition for decision making locally from those already made by regulatory Agencies included into the WHO Listed Authorities (WLA), for PAC´s approval.